Seismic Qualification: An Approach for Safe Power System During Earthquakes (Journal of Science and Engineering, 2026)
Earthquakes have caused many catastrophes in the past. Construction industries, electrical industries and people should be aware of the danger and prepared against earthquakes by constructing earthquake resistant structures. Past earthquake data reveals electrical and telecommunication facilities are seismically vulnerable and susceptible to failure due to seismic dynamic loading. High voltage substation equipments are most vulnerable in electrical and telecommunication facilities. Demand for electric power supply during post-earthquake and safety of consumers emphasize the need for seismic reliable electrical power system. For reliable power supply during and after earthquakes electrical equipment shall be seismically qualified before installation. Basics of seismic qualification of electrical equipment, procedure of qualification and relevant codal provisions are presented in this paper.